Quantitative approach by miospores of the Devonian-Carboniferous transition - Streel, Maurice; Di Pasquo Lartigue, Maria
The abundance of selected species at geological scale has been noted to be a useful criterium to correlate sedimentary sequences. In this work, we take as an example two groups of species, the lepidophyta and pusillites, which are noted to characterize the Devonian-Carboniferous transition. From formerly obtained results in rare Famennian coal-beds, it is known that the parent plants of the two groups of spores were living near swamps in deltaic marshes. Spores (miospores), often with diameters around 50 µm, have the advantage, compared to other microfossils, to be produced by each individual terrestrial plant in thousands of specimens, which are transported into the sediments by wind and fluvial or marine currents. In this context, the group lepidophyta, the most widespread and stratigraphically narrowest, was chosen to be considered in priority. We selected the geological sections studied in the northern Rhenish Massif (Sauerland, Germany) as reference because they are the best known for animal macrofossils, such as goniatites, in particular those species that had been used to fix the DCB before the use of conodonts (and spores), which prevail to-day. In the reference sections in Sauerland, the extinction of the group lepidophyta is observed in two steps. Initially it is most often dominant, with more than 50 % of the total of all spores counted. The first extinction step is characterized by a strong decline of the group lepidophyta, which persist to be present in all samples, but rarely exceeds 5 % of the total of all spores counted. The second extinction step led to the complete absence of the group. These two extinction steps have been noted in several localities in Europe (Ireland, England, Poland, Portugal) but also in Greenland in a sedimentary sequence in which the extinction of the group lepidophyta is linked to warming and humidity increase and the collapse of the final Devonian glacial episode. We have searched this interval in North and South America, but most of palynological analysis have no ...